The potential capacity of hamlets - Vries, Michiel S. de (Central European Public Administration Review, 2019)
The main theories on small municipalities and the practices as seen in many a country involving the consolidation thereof presume that the contextual and structural conditions under which small municipalities have to perform work to their detriment and pose a threat to their viability. However, the institutional and human resource conditions in which small municipalities operate might work both ways, being profitable as well as disadvantageous. This paper investigates what is theoretically known and can be empirically deduced about the capacity of small municipalities in Europe. The conclusion is that existing research is inconclusive in its outcomes regarding the actual capacity of so-called hamlets and that existing data related to local capacity are unfit to measure such among these small municipalities. Nonetheless, the paper concludes that although no conclusions can be drawn on the actual capacity of small municipalities, their potential capacity is significant. This is concluded based on their legal protection, their inclination to focus on a limited number of policy areas, their access to central and regional decision-making, and especially the trust they receive from their residents.
Keywords: majhne občine; pogoji; uspešnost; zaselki; zaupanje; zmogljivost